2021
DOI: 10.1007/s10926-021-09960-z
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Outcomes of the Individual Placement and Support Model in Subgroups of Diagnoses, Substance Abuse, and Forensic Conditions: A Systematic Review and Analysis of Pooled Original Data

Abstract: Purpose To investigate the effect of Individual Placement and Support (IPS) according to diagnoses of schizophrenia, bipolar disorder, major depression, substance use disorders, or forensic psychiatric conditions. Methods A systematic search of the literature was conducted in June 2017 and repeated in December 2020. The systematic review included 13 studies. Analyses of pooled original data were based on the six studies providing data (n = 1594). No studies on forensic psychiatric conditions were eligible. Hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 34 publications
(100 reference statements)
0
23
0
Order By: Relevance
“…If in the long‐term IPS can achieve better mental (and physical) outcomes while reducing long‐term welfare dependency (Holmås et al, 2021) there are potential economic benefits to both the health sector and PES. Based on the efficacy of IPS for people with moderate to SMI, the approach is rapidly expanding into other client populations around the world (Hellström et al, 2021; Probyn et al, 2021). Research will be critical to the understand whether adaptations or adjustments to the existing IPS principles are needed for these populations.…”
Section: Implications For Policymentioning
confidence: 99%
“…If in the long‐term IPS can achieve better mental (and physical) outcomes while reducing long‐term welfare dependency (Holmås et al, 2021) there are potential economic benefits to both the health sector and PES. Based on the efficacy of IPS for people with moderate to SMI, the approach is rapidly expanding into other client populations around the world (Hellström et al, 2021; Probyn et al, 2021). Research will be critical to the understand whether adaptations or adjustments to the existing IPS principles are needed for these populations.…”
Section: Implications For Policymentioning
confidence: 99%
“…Individualized support is perceived by people with mental illnesses seeking employment as an important facilitating factor, which is a challenging task for social workers and clinicians involved in IPS programs (77,78). The type of mental disorder can also affect program's efficacy for different outcomes (21). External emotional support from peers and family members is critical for rehabilitation and recovery (42,79).…”
Section: Barriers and Facilitators Of Successful Ips Implementation And Employmentmentioning
confidence: 99%
“…Type of the mental issue is also critical as it seems to be more effective in some disorders and less and in others (21,84). A systematic review of studies assessing IPS efficacy in individuals with substance use disorders found that episodic treatment of the disease and risk of relapse of the mental disease were among important barriers in implementing IPS (22).…”
Section: Barriers and Facilitators Of Successful Ips Implementation And Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicated the beneficial effects of IPS for people with PTSD and SUD (Bond et al ., 2019). However, mixed indications of the effectiveness of IPS for people with CMD (including affective disorders) were found (Hellström et al ., 2021; Probyn et al ., 2021). The reasons for the diminished effectiveness of IPS for CMD are unclear, because a consistent definition of CMD is lacking.…”
Section: Introductionmentioning
confidence: 99%